2020
DOI: 10.4081/ijfs.2020.9055
|View full text |Cite
|
Sign up to set email alerts
|

A representative sampling of tuna muscle for mercury control

Abstract: The mechanisms of mercury accumulation and distribution in fish tissues are related to its high affinity for sulfhydryl groups in proteins. There is evidence that mercury is distributed unevenly based on the different reactivity of these groups in the various muscle proteins. Tuna fish also shows numerous specialized anatomical features including the structure of the swimming muscles and some form of endothermy, which generates variations in the mercury content between dark and white muscle and between muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…The present study shows that, even in the case of Atlantic bluefin tuna, the canning process promotes a statistically significant increase in the concentration of mercury from raw samples to canned samples. The re-sults of the present study showed that also in Atlantic bluefin tuna, like Southern bluefin tuna [1][2][3][4][6][7][8][9]13,[15][16][17][18][19][20][21][22][23][24][25]29,31] and Pacific bluefin tuna [23], the weight of fish represents the best known, but not the only, variable associated with the dynamics of mercury accumulation in the muscles. In fact, at least two other components must be considered: K and the percentage of fat in the muscle.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The present study shows that, even in the case of Atlantic bluefin tuna, the canning process promotes a statistically significant increase in the concentration of mercury from raw samples to canned samples. The re-sults of the present study showed that also in Atlantic bluefin tuna, like Southern bluefin tuna [1][2][3][4][6][7][8][9]13,[15][16][17][18][19][20][21][22][23][24][25]29,31] and Pacific bluefin tuna [23], the weight of fish represents the best known, but not the only, variable associated with the dynamics of mercury accumulation in the muscles. In fact, at least two other components must be considered: K and the percentage of fat in the muscle.…”
Section: Discussionmentioning
confidence: 86%
“…In order to comply with the official methods of sampling and analysis for the control of the levels of contaminants in foodstuffs [18], a division in homogeneous sub-lots in relation to size and age of the specimens was carried out. The correlation between size and age of tuna was evaluated according to previous studies [8,9,[21][22][23][24][25]29,31,32]. It was found that 78.6% of the batch (n. 213 specimens) consisted of "very young" tuna, estimated to be up to 5 years old (weight range: 20.2-55.4 kg, mean ± standard deviation (s.d.…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Тому ВООЗ рекомендує проводити відповідні дослідження та вживати усіх можливих заходів для зниження рівнів метилртуті в продуктах харчування, особливо у рибі. Це дозволять споживачам приймати рішення щодо видів та кількості морепродуктів, які є безпеч-ними для вживання та корисними з точки зору харчування (Balshaw et al, 2007;Bosch et al, 2016;Zupo et al, 2019;Annibaldi et al, 2019;Piras et al, 2020).…”
Section: вступunclassified